Non-suicidal self-injury among women hospitalised for anorexia nervosa - Hirot, France; Ali, Aminata; Blanchet, Corinne; Grandclerc, Salomé; Gicquel, Ludovic; Berthoz, Sylvie; Godart, Nathalie (Eating and weight disorders, 2025)
Introduction Non-suicidal self-injury (NSSI) is frequent in eating disorders (ED). The aim of this study was to describe NSSI among subjects hospitalised for anorexia nervosa (AN) who self-harm and factors associated with NSSI in this population. Methods This study was part of a larger French longitudinal multi-centre study. Two hundred and two women with AN were recruited from inpatient treatment facilities for ED from 2009 to 2011. All participants fulfilled the DSM-5 diagnostic criteria of AN. Subjects with and without NSSI were compared for clinical characteristics and comorbidities in bivariate analyses. Logistic regression analysis was then used to identify factors associated with NSSI. Results The mean age of the sample was 20.8 years (± 6.6). The mean BMI was 14.3 (± 1.5). Overall 36.1% had self-harmed in the past 6 months. The main factors that triggered NSSI were a feeling of physical or psychological unease (45.2%), feelings of anger (24.7%), an attempt to relieve discomfort (19.2%), and low self-esteem (16.4%). Lifetime major depressive disorder, suicide attempts and eating concerns were independently associated with NSSI. Discussion ED symptoms were linked to NSSI, but psychiatric history also played a key role. This is consistent with hypotheses of common underlying transdiagnostic mechanisms linking emotional dysregulation to NSSI and ED. Level of evidence Level III, well-designed cohort or case–control analytic studies.